Hambatan dan Inovasi Dalam Implementasi Standar Akuntansi Pemerintahan Terhadap Laporan Keuangan - Jelita Yulianti Br Sitanggang; Lestari Br Tohang; Yuliana Simatupang; Nasirwan Nasirwan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the implementation of Government Accounting Standards (SAP) in government financial reports and the challenges in its implementation. SAP plays a role in creating a financial system that is transparent, accountable, and in accordance with good governance. However, its implementation faces obstacles such as limited human resources, resistance to change, and the complexity of regulations at the central and regional levels.The lack of understanding of SAP by state officials is an obstacle due to the lack of training and certification. In addition, the work culture that has been formed and the lack of socialization have made many agencies still maintain conventional reporting systems that are less transparent. The complexity of regulations is also a challenge for local governments in adopting this standard optimally.To overcome these obstacles, it is necessary to increase the capacity of human resources through training and certification, the use of digital technology in accounting systems, and digital-based applications for real-time monitoring of financial reports. This step aims to increase the effectiveness, efficiency, and transparency in state financial management.The success of SAP implementation depends on the readiness of human resources, management support, and technology in financial recording and reporting. Optimizing SAP will improve the quality of government financial reports, support better governance, and increase public trust in state financial management